Intrinsic charge polarization in Bi19S27Cl3 nanorods promotes selective C-C coupling reaction during photoreduction of CO2 to ethanol - Das, Kousik; Das, Risov; Riyaz, Mohd; Parui, Arko; Bagchi, Debabrata; Singh, Ashutosh Kumar; Singh, Abhishek Kumar; Vinod, Chathakudath P.; Peter, Sebastian C. (Advanced Materials, 2023)
Obtaining multi-carbon products via CO2 photoreduction is a major catalytic challenge involving multielectron-mediated C-C bond formation. Complex design of multicomponent interfaces that are exploited to achieve this chemical transformation, often leads to untraceable deleterious changes in the interfacial chemical environment affecting CO2 conversion efficiency and product selectivity. Alternatively, robust metal centers having asymmetric charge distribution can effectuate C-C coupling reaction through the stabilization of intermediates, for desired product selectivity. However, generating inherent charge distribution in a single component catalyst is a difficult material design challenge. Here, a novel photocatalyst, Bi19S27Cl3, is presented which selectively converts CO2 to a C-2 product, ethanol, in high yield under visible light irradiation. Structural analysis through transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, and X-ray absorption spectroscopy reveals the presence of charge polarized bismuth centers in Bi19S27Cl3. The intrinsic electric field induced by charge polarized bismuth centers renders better separation efficiency of photogenerated electron-hole pair. Furthermore, charge polarized centers yield better adsorption of CO* intermediate and accelerate the rate determining C-C coupling step through the formation of OCCOH intermediate. Formation of these intermediates is experimentally mapped by in situ Fourier-transform infrared spectroscopy and further confirmed by theoretical calculation.
Keywords: C-C coupling; charge polarization; CO2 reduction; Ethanol; Photocatalysis